Problem konieczności wypełnienia warunków dotyczących stron umowy małżeńskiej określonych przez ustawodawstwo Kościoła Polskokatolickiego w przypadku zawierania małżeństwa mieszanego przez katolika w Kościele Polskokatolickim - Dzierżon, Ginter (Ius Matrimoniale, 2014)
The analyses presented in the article show that the obligations regarding the contracting parties codified in § 63, n. 1-3 of „Marriage Law of the Polish Catholic Church” do not in general collide with the requirements specified by the legislator in can. 1125, n. 1-3 CIC. Therefore, meeting the obligations by the Catholic party does not contradict the doctrinal approach of Roman Catholic Church to the issue of mixed marriages. The author believes that if a Catholic is willing to enter into marriage with a member of Polish Catholic Church, the marital contract enters the juridic area of the Polish Catholic legislator. It is this legislator that has the right to specify, according to his own system presumptions, the conditions necessary to contract this type of marriage which, in consequence, should be fulfilled by the Catholic party.